(untitled) (Communications in Computational Physics, 2022)
In this paper, we propose a local discontinuous Galerkin (LDG) method for the multi-dimensional stochastic Cahn-Hilliard type equation in a general form, which involves second-order derivative ∆u in the multiplicative noise. The stability of our scheme is proved for arbitrary polygonal domain with triangular meshes. We get the sub-optimal error estimate O(h^k) if the Cartesian meshes with Q^k elements are used. Numerical examples are given to display the performance of the LDG method.